1998
DOI: 10.1007/s004240050673
|View full text |Cite
|
Sign up to set email alerts
|

Hypotonically induced calcium increase and regulatory volume decrease in newborn rat cardiomyocytes

Abstract: The effect of cell swelling on intracellular calcium concentration ([Ca2+]i) was studied in newborn rat cardiomyocytes. Hypotonic cell swelling induced a fast and transient [Ca2+]i increase (hypotonically induced calcium increase, HICI; 388±47 nM, n=14). HICI was not inhibited by cyclopiazonic acid (CPA), an inhibitor of sarcoplasmic Ca2+-ATPase, nor ryanodine (an inhibitor of calcium-induced calcium release), whereas it was abolished (11±19 nM, n=5) in the absence of external calcium. Thus, HICI appeared to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…RVD is dependent on increases in plasma membrane Ca 2+ influx in various tissues [16,51,52]. We first determined whether such influx is also required for RVD in HCEC.…”
Section: Trpv4 Channel Activation Mediates Rvdmentioning
confidence: 99%
“…RVD is dependent on increases in plasma membrane Ca 2+ influx in various tissues [16,51,52]. We first determined whether such influx is also required for RVD in HCEC.…”
Section: Trpv4 Channel Activation Mediates Rvdmentioning
confidence: 99%
“…Under ruptured patch voltage-clamp conditions, for example, swelling is reported to enhance I Ca-L in rabbit atrial and sinoatrial node cells (22), depress I Ca-L in rat ventricular cells (4), and to have no significant effect in guinea pig (13,31) and canine (44) ventricular cells. A swelling-induced enhancement of I Ca-L also has been claimed based on fura 2 measurements of diltiazem-sensitive Ca 2ϩ influx (36). It is unclear whether these differences in the response of I Ca-L to myocyte swelling arise from species differences or from methodological issues, such as the composition of the patch pipette solution, the effectiveness of cell dialysis, or the variable extent of myocyte swelling under ruptured-patch conditions (6,33).…”
mentioning
confidence: 99%
“…There are controversies in the literature regarding how cell swelling can modulate cardiac I Ca,L channel. For example, I Ca,L increases in neonatal rat ventricular myocytes [14] and rabbit sinoatrial node and atrial cells [12,13] , remains unaltered in canine ventricular myocytes [17] , decreases or remains unaltered in guinea-pig ventricular myocytes [10,15] . Brette et al had reported that in rat ventricular myocytes osmotic swelling decreases I Ca,L [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have even demonstrated biphasic effects on I Ca,L , an increase followed by a more sustained decrease [18] . Previous reports indicated that osmotic swelling increases I Ca,L in neonatal rat ventricular myocytes [14] , but decreases I Ca,L in adult rat ventricular myocytes [16] . But these reports did not explore the mechanism underlying the changes of I Ca,L .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation